The price of doubt - Nathan, N. M. L. (International library of philosophy., 2001)
"An argument may fail because it is unsound. A trivial conclusion is another fault. Do all the sceptic's arguments have one or both of these deficiencies? This book conjectures that they do. Some sceptical arguments are entirely sound. Some have non-trivial conclusions. But none, it is conjectured, has both of these advantages."